The Development of Gamification-Based Qur'an Learning Media Using Wordwall at SMK Muhammadiyah 3 Singosari, Indonesia - Sya'roni Al Fajri (KURAS Institute, 2025)
This study aims to develop a gamification-based Al-Qur'an learning medium through the Wordwall platform with the theme of Fastabiqul Khoirot for grade X students at SMK Muhammadiyah 3 Singosari. Al-Qur'an learning faces challenges in student engagement due to monotonous teaching methods. This development research uses the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) with a gamification approach that integrates game elements into learning. The resulting product is named